2014
DOI: 10.4047/jap.2014.6.5.415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the translucency of shaded zirconia all-ceramic systems

Abstract: PURPOSEThe purpose of this study was to evaluate and compare the translucency of shaded zirconia all-ceramic systems.MATERIALS AND METHODSTranslucency of 3 different zirconia all-ceramic systems colored by different techniques was compared with a lithium disilicate glass-ceramic (IPS e.max Press). Square-shaped specimens with 0.5 mm thickness were fabricated from In-Ceram YZ, ICE Zirkon and Katana systems in A1, A2 and A3.5 shades according to Vitapan Classical shade tab (n=11). Specimens were then veneered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 29 publications
6
46
2
3
Order By: Relevance
“…In addition, pigmentation has been reported to inversely affect translucency. 48 It could be hypothesized that the absence of significant differences between layers in the present investigation can be attributed to lower lightness associated with higher chromaticity in the first two layers, DEL and FTL, vs greater lightness associated with less pigmentation in the last two layers, STL and ENL. Thickness has been confirmed as a major factor in the translucency of a material.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, pigmentation has been reported to inversely affect translucency. 48 It could be hypothesized that the absence of significant differences between layers in the present investigation can be attributed to lower lightness associated with higher chromaticity in the first two layers, DEL and FTL, vs greater lightness associated with less pigmentation in the last two layers, STL and ENL. Thickness has been confirmed as a major factor in the translucency of a material.…”
Section: Discussionmentioning
confidence: 57%
“…43 Moreover, having a higher chromaticity, they tend to be more affected by increasing thickness. 48 It can be suggested that the four-layered UTML at 0.4 or 0.6 mm thicknesses could be a suitable restorative material for veneers. To the best of our knowledge, the application of digital image analysis with the CIE L*a*b* coordinates system to evaluate translucency has not been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lithium disilicate ceramics have improved flexural strength because of an increased crystal content of about 70% and refined crystal size, which provides superior translucent properties even with the higher crystal content due to the relatively low refractive index 7) . Zirconia ceramics have significantly higher flexural strength and fracture toughness than the other dental ceramic materials 7,8) , but have poorer translucent properties with a higher refractive index 9,10) . The clinical success of ceramic restorations depend upon the bonding abilities between resin cement and ceramic materials as well as between resin cement and tooth substrates, because they can reduce recurrent caries and post-operative sensitivity by preventing marginal leakage, and protect against fracture of tooth and the restorative materials 11) .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, TP for glass-ceramic veneered and glazed specimens was 12 ±1.1 and for zirconia veneered and glazed specimens 8 ± 0.7. Significantly higher rate of translucency in lithium disilicate glass ceramic in comparison to the zirconia ceramics was also found in Baldissara et al, Kurtulmus-Yilmaz et al and many others (18)(19)(20)(21). This finding can be attributed to the crystalline content of zirconia in order to achieve a greater strength results, but at the same time the inhomogeneity of crystals causes different refractive indices and therefore poor translucency (22,23).…”
Section: Discussionmentioning
confidence: 69%
“…U našem istraživanju parametar translucencije za slojevane i glazirane staklokeramičke uzorke bio je od 12 +/-1,1, a za slojevane i glazirane cirkonij-dioksidne uzorke od 8 +/-7. Kako ističu Baldissara i suradnici te i Kurtlmus-Yilmaz i njegovi kolege, pronađen je značajno veći stupanj translucencije kod litijdisilikatne staklokeramike u usporedbi s cirkonij-dioksidnom keramikom (18,21). Ovaj nalaz može se pripisati kristalnom svojstvu cirkonij-dioksidne keramike, što pridonosi boljoj čvr-stoći materijala, ali istodobno nehomogenost kristala uzrokuje različite indekse loma i lošu translucenciju (22,23).…”
Section: Raspravaunclassified